COMITE ORGANISATEUR/ORGANIZING COMMITTEE - Deschatelets, Gilles; Gharbl, Monique; Lemay, Philippe; Aubin, Alain; Ricard, Michel; Lessard, Gabriel; Morel, Jean; Lefebvre, Marcel; Dagepais, Michel; Turmei, Jacques; et al. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF